2010
DOI: 10.1266/ggs.85.19
|View full text |Cite
|
Sign up to set email alerts
|

Dissection of barley chromosome 4H in common wheat by the gametocidal system and cytological mapping of chromosome 4H with EST markers

Abstract: We used two gametocidal (Gc) chromosomes 2C and 3CSAT to dissect barley chromosome 4H added to common wheat. The Gc chromosome induced chromosomal structural rearrangements in the progeny of the 4H addition line of common wheat carrying the monosomic Gc chromosome. We conducted in situ hybridization to select plants carrying rearranged 4H chromosomes and characterized the rearranged chromosomes by sequential C-banding and in situ hybridization. We established 60 dissection lines of common wheat carrying single… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
16
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
5
4

Relationship

3
6

Authors

Journals

citations
Cited by 26 publications
(16 citation statements)
references
References 32 publications
(32 reference statements)
0
16
0
Order By: Relevance
“…40% of the 2HL arm. These facts suggested that the EST markers or genes on chromosomes 2H were more abundant in the distal region than in the proximal region in either arm, as observed for the other barley chromosomes (Künzel et al, 2000;Nasuda et al, 2005;Ashida et al, 2007;Sakai et al, 2009;Sakata et al, 2010). This tendency was obvious in the subtelomeric regions.…”
Section: Cytological Mapping Of Barley Est Markersmentioning
confidence: 63%
See 1 more Smart Citation
“…40% of the 2HL arm. These facts suggested that the EST markers or genes on chromosomes 2H were more abundant in the distal region than in the proximal region in either arm, as observed for the other barley chromosomes (Künzel et al, 2000;Nasuda et al, 2005;Ashida et al, 2007;Sakai et al, 2009;Sakata et al, 2010). This tendency was obvious in the subtelomeric regions.…”
Section: Cytological Mapping Of Barley Est Markersmentioning
confidence: 63%
“…Using the Gc chromosome as a tool of chromosome manipulation, Endo and Gill (1996) produced an array of deletion stocks of common wheat, Endo (1999, 2000) proved the possibility of producing deletion stocks of barley chromosomes in the genetic background of common wheat, and Endo et al (1994) and Friebe et al (2000) demonstrated that the Gc system induce rearrangements in rye chromosomes added to common wheat. Using the Gc system different researchers so far produced arrays of barley dissection lines of common wheat carrying rearranged chromosomes containing barley chromatin derived from single barley chromosomes and constructed cytological maps for barley chromosomes: 3H with ESTs (Sakai et al, 2009), 4H with ESTs (Sakata et al, 2010), 5H with ESTs (Ashida et al, 2007), 7H with AFLPs and STSs (Serizawa et al, 2001), 7H with AFLPs and SSRs (Masoudi-Nejad et al, 2005), and 7H with ESTs .…”
Section: Introductionmentioning
confidence: 99%
“…Using the Gc system, Endo and his colleagues have dissected the barley chromosomes in the addition lines of common wheat (Shi and Endo, 1997, 1999, and constructed cytological maps for five barley chromosomes using various DNA markers: 2H with ESTs (Joshi et al, 2011), 3H with ESTs (Sakai et al, 2009), 4H with ESTs (Sakata et al, 2010), 5H with ESTs (Ashida et al, 2007), 7H with AFLPs and STSs (Serizawa et al, 2001), 7H with AFLPs and SSR (Masoudi-Nejad et al, 2005), and 7H with ESTs .…”
Section: Introductionmentioning
confidence: 99%
“…Till now, cytological maps, the lowest-resolution physical chromosome maps, have been constructed in common wheat (Triticum aestivum L. 2n = 6x = 42, AABBDD) (Werner et al, 1992;Kota et al, 1993;Delaney et al, 1995aDelaney et al, , 1995bMickelson-Young et al, 1995;Gill et al, 1996aGill et al, , 1996bRandhawa et al, 2004;Hossain et al, 2004;Qi et al, 2004) by using a series of the deletion stocks of common wheat (Endo and Gill, 1996). Cytological maps have also been constructed in barley (Hordeum vulgare L., 2n = 2x = 14, HH) by using a series of dissection lines of common wheat carrying barley deletion chromosomes or barley-wheat translocations (Shi and Endo, 1999;Nasuda et al, 2005;Ashida et al, 2007;Sakai et al, 2009;Sakata et al, 2010;Joshi et al, 2011). The wheat stocks and alien dissection lines were generated by the gametocidal (Gc) system using chromosomes 2C from Aegilops cylindrica or 3C…”
Section: Introductionmentioning
confidence: 99%